The Study of urban drainage system based on spatial structure plan - Rahmat Irawan; Ellina S. Pandebesie; Ipung Fitri Purwanti (Center for Science and Technology, IAIN Surakarta, 2017)
The whole planning of urban infrastructure development should refer to the Detailed Spatial Planning that has been developed by the Regional Government. One of them is the drainage system planning which also needs to pay attention to the land use change plan. This change would cause an increase of run-off coefficient as a result of the increasing number of structure-covered land. Based on the land use planning of Spatial Structure Planning 2034, there was an increase in land cover with a total area of 75 hectares. Therefore, it is necessary to evaluate the urban drainage system in order to avoid problems in the future. Flood discharge was calculated using the rational formula applying run-off coefficient according to spatial structure plan. The analysis of the existing drainage system was carried out to find out whether it is still capable of accommodating the discharge according to Spatial Structure Planning 2034. Based on the drainage channel capacity analysis, 30 existing channels have to be repaired. They must be adjusted by widening the channel and increase the number of channels by 3191.36 m. Another effort to reduce the flood is by making 179 absorption wells in residential areas.